Methodology of Construction and Design of Ontologies: a Case Study of Scientometrics Field - Morteza Mohammadi Ostani; Maryam Azargoon; Mozaffar Cheshmesohrabi (Iranian Journal of Information Processing & Management, 2018)
Ontology is a useful tool for organizing resources and on the other hand is a useful tool for the knowledge representation. With the development of semantic web technologies, building and creating ontologies to expedite the process is necessary. The aim of the study is to explain the situation of methodologies, designing scientometrics conceptual model, and steps of ontology construction as ScientometricsOnt. The method of the study is applied research. The research population of the study is book, article, glossary, thesaurus, dissertation, and research projects of the field of scientometrics in Persian language. To collect terms internal databases are used and related resources are searched. For creating scientometrics conceptual model and explaining relationships and individuals domain analysis approach is used. The reliability and validity of scientometrics conceptual model have been approved by experts in the field of scientometrics. The tool for building ontology is Protégé 5 software. The used methodology was OAsys method Bermejo (2007) with some changes. The results revealed that Ontology of scientometrics was formed in eleven major class which has 20 relationships and 100 individuals. This ontology can be a very useful tool for better knowledge representation in this field. Also, Scientometrics ontology can be a basis for extending and developing terms and future concepts in the field.